Design of Planar Reconfigurable, Tunable, and Wide Angle Resonant Absorbers for Applications in the IR Spectrum. Issue 6 (21st April 2021) - Gomes de Souza, Igor Leonardo; Rodriguez‐Esquerre, Vitaly Felix; Alves Oliveira, Israel
Abstract: A hybrid resonant absorber Fabry Perot—FP tunable from a simple stack of planar layers of ultra‐thin films of phase change material is proposed, designed, and demonstrated numerically. This work shows that properly designed metal–dielectric–metal) structures comprising thin films of titanium (Ti), germanium telluride (GeTe) on a silver (Ag) substrate produce a dynamic modulation of light in the near IR with almost perfect absorption ( A > 93%). It is demonstrated that the resonant peaks of the hybrid absorber can be tuned in two different ways for any wavelength, with the crystallization fractions and the thickness of the dielectric. The influence of the metallic top layer thickness is also analyzed and demonstrated the fabrication error tolerance of the proposed absorber is demonstrated. Also analyzed is the influence of the thickness of the metallic top layer and tolerance to fabrication error of the proposed absorber is demonstrated. Finally, the physical mechanisms for the coupling of the electromagnetic field and the absorbed optical power in the structure proposed are presented and discussed. This study allows the beginning of the development of hybrid devices to control the absorption of light in the region of the electromagnetic spectrum used in optical communications. Abstract : This paper shows a tunable FP hybrid resonant absorber. A MIM structure, with PCM as an insulator, is used. It is possible to control the resonance peaks of the structure with the crystallization fraction of GeTe. This study allows the development of hybrid devices for the control of absorption in the region of the spectrum used in optical communications.